An Empirical Study in Albania of Foreign Direct Investments and Economic Growth Relationship - Cakerri, Lorena; Muharremi, Oltiana; Madani, Filloreta (International Journal of Economics and Financial Issues, 2020)
Albania has managed to attract increasing foreign direct investments (FDI) inflows as a result of achieving political and macroeconomic stability, improving the business climate and legislation. FDI is an essential source of sustained economic growth for Albania, bringing in capital investment, advanced technology, and highly qualified management. FDIs have helped the country finance existing account deficits, further develop the financial sector, and increase employment possibilities. This paper aims to study the empirical relationship between FDI and economic growth in Albania from 2002 to 2017 using time series data. This research will assess whether the inflow from foreign direct investors into Albania has created a positive cointegration relationship on economic growth. Keywords: Foreign Direct Investment, economic growth, development, cointegration, VECM. JEL Classifications: F21, F43, C23, 010 DOI: https://doi.org/10.32479/ijefi.9294